Cumulative live birth rate in women aged ≤37 years after in vitro fertilization with or without preimplantation genetic testing for aneuploidy: a Society for Assisted Reproductive Technology Clinic Outcome Reporting System retrospective analysis - Rachel B. Mejia, D.O; Emily A. Capper, B.A; Karen M. Summers, M.P.H., C.H.E.S; Abigail C. Mancuso, M.D; Amy E. Sparks, Ph.D; Bradley J. Van Voorhis, M.D (Elsevier, 2022)
Objective: To investigate cumulative live birth rates (CLBRs) in cycles with and without preimplantation genetic testing for aneuploidy (PGT-A) among patients aged <35 and 35-37 years. Design: Retrospective cohort study. Setting: Society for Assisted Reproductive Technology reporting clinics. Patient(s): A total of 31,900 patients aged ≤ 37 years with initial oocyte retrievals between January 2014 and December 2015 followed through December 2016. Intervention(s): None. Main outcome measure(s): The primary outcome was CLBR among patients aged <35 and 35-37 years. The secondary outcomes included multifetal births, miscarriage, preterm birth, perinatal mortality, and the time to pregnancy resulting in a live birth. Adjusted odds ratios (aORs) adjusting for age, body mass index, total 2 pronuclei embryos, embryos transferred, and follow-up timeframe. Result(s): Among patients aged <35 years, PGT-A was associated with reduced CLBRs (70.6% vs. 71.1%; aOR, 0.82; 95% CI [confidence interval], 0.72-0.93). No association was found between PGT-A and CLBRs among patients aged 35-37 years (66.6% vs. 62.5%; aOR, 0.92; 95% CI, 0.83-1.01). Overall, there was no significant difference in the miscarriage rate (aOR, 0.97; 95% CI, 0.82-1.14). Multifetal birth rates were lower with PGT-A (9.5% vs. 23.1%); however, PGT-A was not an independent predictor of multifetal birth (aOR, 1.11; 95% CI, 0.91-1.36). The average time to pregnancy resulting in a live birth was 2.37 months (SD 3.20) for untested transfers vs. 4.58 months (SD 3.53) for PGT-A transfers. Conclusion(s): In women aged <35, the CLBR was lower with PGT-A than with the transfer of untested embryos. In women aged 35-37 years, PGT-A did not improve CLBRs.